Self-perception of childrenś oral health by their parents. (20th October 2021) - Veiga, N; Carvalho, A; Correia, P; Couto, P; Correia, MJ
Abstract: Background: Neglecting oral hygiene can lead to early tooth loss, pain, discomfort and, consequently, a great monetary investment to repair the damage caused in the stomatognathic system, whether of masticatory, phonetic or aesthetic origin. The aim of the present study consists in the characterization of oral health perception and oral hygiene habits of the children by their own parents and the creation of a scale to classify children's oral health perception by their parents. Methods: A cross-sectional observational epidemiological study was performed. The population of this study was made up of 422 parents whose children are between five and eleven years of age and who attend schools in the districts of Viseu and Lisbon. The data collection was achieved through the application of a self-administered questionnaire in order to characterize the parentś perception of the oral health of their own children. Results: Through the analysis of the questionnaires, 54.8% of the sample considered that their own children present inadequate oral health behaviors; 40.3% sufficient and only 4.8% consider that their children have good and adequate oral health behaviors. Regarding oral hygiene, most of the children did it one to five times a day, 44.7% took '2 minutes' to perform this activity, 70.3% did not use dental floss, 77.9% do not brush their teeth after lunch, 49.3% only use toothbrush for oral hygiene, 13.6% never went to the dentist, 26.9% are afraid, 38.1% have already suffered from toothache, 28.8% had gingival hemorrhage and 12.6% had gingival inflammation. Conclusions: Oral health is a determining factor for a good quality of life. To this end, it is essential to implement oral health education and promotion strategies with all members of the household, in order to guarantee better oral health indexes in the community. Key messages: Oral health literacy and knowledge is essential in order to improve oral health indexes in the community. The characterization of the oral health of children and adolescents is crucial to improve oral health behaviors and establish the correct oral health promotion programs.